The review of autopsy cases of accidental childhood deaths in Istanbul - (:unkn) unknown (ELSEVIER SCI LTD, 2011)
Children are at increased risk for various causes of injury from accidents. Accidents are, by far, the leading cause of death among children and adolescents. The aim of this study is to evaluate the lethal childhood accidents in Istanbul by age groups. Reports of autopsies performed between 2001 and 2005 in the Morgue Department of the Council of Forensic. Medicine in Istanbul (n :16853) are examined retrospectively. 833 deaths from accidents in children aged 0-18 years are investigated into the study. The parameters of age, gender, types of accidents and causes of death are evaluated. The accidents account for 47.3% of the deaths among children aged 0-18 years. Of 833 cases, 601 (73%) are male and 232 (27%) are female. The female to male ratio is 1/2.6. The highest rate of death from accidents is at the group of 15-18 years. The primary causes of accidental childhood deaths are motor vehicle accidents (23.1%), followed by drowning (20.1%), poisoning (15.7%), and fall from height (15.5%). The incidence and types of trauma vary with socio-economic status and culture. Istanbul, where this study is conducted in, has approximately 3000 autopsy number annually. Therefore, it provides an important database. (C) 2011 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Childhood accidents; Autopsy; Forensic medicine; INJURY; MORTALITY; AUSTRALIA; PATTERNS; RATES